1960
DOI: 10.1099/00221287-23-3-613
|View full text |Cite
|
Sign up to set email alerts
|

The Titration of Trachoma and Inclusion Blennorrhoea Viruses in Cell Cultures

Abstract: SUMMARYA technique is described for titrating trachoma and inclusion blennorrhoea viruses by counting the inclusions formed in HeLa cell monolayers. The method compares favourably in accuracy with other techniques used for the assay of viruses and is more reliable than titration in the chick embryo yolk sac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2

Year Published

1963
1963
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 7 publications
1
66
2
Order By: Relevance
“…1). These findings are in line with recent descriptions of trachoma-infected tissue cultures (Gordon, Quan & Trimmer, 1960; Furness, Graham, Reeve & Collier, 1960;Bernkopf et al 1960), and comparable with the earlier accounts of changes that accompany multiplication of other members of the psittacosis group (Bedson & Bland, 1932). The cytopathic changes developed synchronously throughout the cell sheets ; counts indicated that more than 90 yo of the cells were infected a t the outset.…”
Section: Phase-cmtrast Microscopysupporting
confidence: 81%
“…1). These findings are in line with recent descriptions of trachoma-infected tissue cultures (Gordon, Quan & Trimmer, 1960; Furness, Graham, Reeve & Collier, 1960;Bernkopf et al 1960), and comparable with the earlier accounts of changes that accompany multiplication of other members of the psittacosis group (Bedson & Bland, 1932). The cytopathic changes developed synchronously throughout the cell sheets ; counts indicated that more than 90 yo of the cells were infected a t the outset.…”
Section: Phase-cmtrast Microscopysupporting
confidence: 81%
“…HeLa cells were used to propagate Chlamydia trachomatis serovar L2 (LGV 434) for purification using established protocols (35,36). Chlamydial titers were determined using conventional protocols to establish multiplicities of infection (MOI), which were based on inclusion forming units (IFU) and determined in HeLa cells (36,37) using a polyclonal rabbit or guinea pig anti-C. trachomatis serovar L2 EB antibody and secondary antibodies conjugated to DyLight fluors (Jackson ImmunoResearch Laboratories, West Grove, PA). siRNA knock down of syntaxin 6 and VAMP4.…”
Section: Methodsmentioning
confidence: 99%
“…As we noted no differences in the numbers of inclusions formed (specifically, no abrogation of initial entry and infection) in the absence of VAMP4 or syntaxin 6 compared to the numbers of inclusions in controls (data not shown), we wished to assess the impact of these proteins on chlamydial development by examining infectious progeny. To determine infectious progeny, control (nontargeting), VAMP4, or syntaxin 6 siRNA-treated HeLa cells (VAMP4) or C2BBe1 cells (syntaxin 6) were infected with C. trachomatis serovar L2 for 40 to 42 h and lysed, and titers of lysates containing infectious Chlamydia organisms were used to inoculate a fresh monolayer of HeLa cells as previously described (37,45). At 30 h postinoculation, the secondary infections were fixed and processed for indirect immunofluorescence assay.…”
Section: Vamp4 Localization To the Chlamydial Inclusionmentioning
confidence: 99%
“…The infected cells from six batches of 4 1 of infected L cells were homogenized in a Teflon grinder and yielded a total of 3-4 x 1 0~~ inclusion-forming units (i.f.u.) (Furness, Graham & Reeve, 1960;Taverne & Blyth, 1971). The agent was purified by a slight modification of the method of Tamura & Higashi (1963); before and after treatment with nucleases and trypsin, the preparation was centrifuged at 75008 for 60 min at 4 "C through a 6 cm column of 25 yi , * Present address : National Institute for Biological Standards and Control, Holly Hill, Hampstead, London N W 3 6RB.…”
Section: Methodsmentioning
confidence: 99%